2021
DOI: 10.1186/s13148-021-01023-7
|View full text |Cite
|
Sign up to set email alerts
|

BRG1 knockdown inhibits proliferation through multiple cellular pathways in prostate cancer

Abstract: Background BRG1 (encoded by SMARCA4) is a catalytic component of the SWI/SNF chromatin remodelling complex, with key roles in modulating DNA accessibility. Dysregulation of BRG1 is observed, but functionally uncharacterised, in a wide range of malignancies. We have probed the functions of BRG1 on a background of prostate cancer to investigate how BRG1 controls gene expression programmes and cancer cell behaviour. Results Our investigation of SMARCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 100 publications
1
11
0
Order By: Relevance
“…We observed that depletion of the ATPase subunit, BRG1, significantly reduced cell viability both in normoxia, as well as, in hypoxia (Figure 4). Loss of BRG1 has been shown previously by others to be required for cell proliferation 4750 , thus loss of viability is expected, as loss of a catalytic subunit will significantly affect SWI/SNF ability to alter chromatin structure needed for altered gene expression. Knockdown of ARID1A, ARID1B, PBRM1 and BRD9 under normoxic conditions showed no significant reduction in cell viability but interestingly, we observed an increase in cell proliferation when ARID1B and PBRM1 were depleted (Figure 4).…”
Section: Resultsmentioning
confidence: 95%
“…We observed that depletion of the ATPase subunit, BRG1, significantly reduced cell viability both in normoxia, as well as, in hypoxia (Figure 4). Loss of BRG1 has been shown previously by others to be required for cell proliferation 4750 , thus loss of viability is expected, as loss of a catalytic subunit will significantly affect SWI/SNF ability to alter chromatin structure needed for altered gene expression. Knockdown of ARID1A, ARID1B, PBRM1 and BRD9 under normoxic conditions showed no significant reduction in cell viability but interestingly, we observed an increase in cell proliferation when ARID1B and PBRM1 were depleted (Figure 4).…”
Section: Resultsmentioning
confidence: 95%
“…It is well established that Brg1 is an essential effector for the regulation of PCa 28 , 29 , and AR is commonly recognized as a key driver of prostate cancer, even CRPC 3 . Therefore, we hypothesized that Brg1 and AR are both essential substrates for OTUD6A to perform its oncogenic roles in PCa.…”
Section: Resultsmentioning
confidence: 99%
“…GLTSCR1 has only recently been identified as a member of the GBAF SWI/SNF complex (Alpsoy and Dykhuizen 2018), and thus GLTSCR1’s role as a SWI/SNF subunit is not fully understood. Notably, knockdown of another GBAF subunit member, SMARCA4, was shown to reduce cell proliferation and induce cell cycle arrest (Innis and Cabot 2020; Giles et al 2021), a role that may be shared by other GBAF members. Within the 88 co-essential genes, we found a significant enrichment for genes with functions related to regulation of attachment of spindle microtubules to kinetochores (BECNI and SIRT2’ , BH-adjusted p-value = 0.0015) and regulation of exit from mitosis (TGFB1 and SIRT2- , BH-adjusted p-value = 0.0031; Figure 4b; Supplemental Table S5; Methods).…”
Section: Resultsmentioning
confidence: 99%